The genealogy of taubiy Islam (Dadash) Balkarukov - Muslim I. Barazbiev (Кавказология, 2025)
The peoples of the North Caucasus have long prioritized the preservation of genealogical information. In recent decades, there has been an increased interest in such expertise. The purpose of this article is to look into the genealogy of Taubi Islam (Dadasha) Balkarukov, a well-known Karachay-Balkarian aristocrat.The following is based on published materials by travelers and scientists prior to October, as well as the writings of current Russian historians and ethnographers. A large portion of the research is based on documentary sources discovered by the author in the archives of the Kabardino-Balkarian Republic (hereinafter KBR), Krasnodar Territory, and Republic of North Ossetia-Alania (hereinafter RSO-A). The article features a generational painting by Taubiy Balkarukov in a straight falling line. The picture offers information on specific individuals who are Islam’s direct ancestors (Dadasha), as well as himself and his children. Some emphasis is placed on the bond with individuals who played crucial roles in the fates of both Islam’s forebears (Dadash) and himself. The study explores the Balarukovs’ marriage relations with the aristocratic families of Balkaria and Karachay, as well as other peoples from the North Caucasus.Some information about the genealogy of the Taubi Balkarukovs is inconsistent, as evidenced by multiple versions of the legends documented by researchers before to October. Finally, the paper concludes that Islam (Dadasha) Balkarukov’s genealogy gives a lot of data for both professional scientists and history and ethnology enthusiasts to explore. However, this issue requires additional investigation.